2015
DOI: 10.1177/0363546514566193
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Preinjury Sleep Difficulties on Neurocognitive Impairment and Symptoms After Sport-Related Concussion

Abstract: Preinjury sleep difficulties may exacerbate neurocognitive impairment and symptoms after concussion. The findings may help clinicians identify athletes who are at risk for worse impairments after a concussion due to preinjury sleep difficulties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 44 publications
(61 reference statements)
0
29
0
Order By: Relevance
“…37 Sleep disorders in children after traumatic brain injury have been associated with poor functional outcomes. 24,38 Recent research has found athletes with pre-injury sleep difficulties are more symptomatic at baseline 39,40 and during the post-concussive period. 38 Our data support the relationship of pre-injury sleep disorder and prolonged post-concussive symptoms in a sport and non-sport concussed population.…”
Section: Discussionmentioning
confidence: 99%
“…37 Sleep disorders in children after traumatic brain injury have been associated with poor functional outcomes. 24,38 Recent research has found athletes with pre-injury sleep difficulties are more symptomatic at baseline 39,40 and during the post-concussive period. 38 Our data support the relationship of pre-injury sleep disorder and prolonged post-concussive symptoms in a sport and non-sport concussed population.…”
Section: Discussionmentioning
confidence: 99%
“…While factors such as age, severity of trauma, number of prior traumatic brain injuries and timing of prior TBI have been shown to impact the outcome of neurocognitive testing, few studies have evaluated the impact of sleep on recovery (Albrecht et al 2016;Gaudet and Weyandt 2017;Martindale et al 2017;Lau et al 2011;Sufrinko et al 2015;Singh et al 2016). Of these, one study (n = 348) demonstrated that patients with insomnia and reduced sleep times prior to TBI have a prolonged recovery post-injury as measured by the Immediate Post-concussion Assessment and Cognitive Test and Post-concussion Symptom Scale when compared to controls (Sufrinko et al 2015).…”
Section: Sleep and Neurocognitionmentioning
confidence: 99%
“…Of these, one study (n = 348) demonstrated that patients with insomnia and reduced sleep times prior to TBI have a prolonged recovery post-injury as measured by the Immediate Post-concussion Assessment and Cognitive Test and Post-concussion Symptom Scale when compared to controls (Sufrinko et al 2015). Another study demonstrated that poor sleep quality independently predicted cognitive dysfunction in post-TBI combat veterans when controlling for other variables such as PTSD, while others have corroborated that poor sleep prolonged cognitive recovery from TBI in non-combat patients (Martindale et al 2017;Singh et al 2016).…”
Section: Sleep and Neurocognitionmentioning
confidence: 99%
“…6,7,34 This group has also focused on sex differences in presentation and recovery, clinical assessments, and predictor of prolonged recovery from SRC. 35,36 University of Michigan was the final hub (n=11) identified in this analysis, whose publication focused on the utility and efficacy of clinical assessments 37 and the role of biomechanics/head impacts. 38 Together, these institutions represent the most prolific hubs of SRC research over the previous decade.…”
Section: Institutions and Authorsmentioning
confidence: 99%